2000
DOI: 10.1590/s1516-31802000000400006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Gardnerella vaginalis, Candida sp and human papilloma virus in cytological smears

Abstract: a b s t r a c t CONTEXT:In spite of the wide-ranging literature on the microbiology of normal and abnormal flora of the vagina, there are few studies on the relationship between human papilloma virus (HPV) and other vaginal microorganisms. OBJECTIVE:To analyze the frequency of infection by human papilloma virus (HPV) and other agents like Candida sp., Gardnerella vaginalis and Trichomonas vaginalis in cytological smears. DESIGN STUDY: Retrospective study SETTING:A public tertiary referral center. SAMPLE:An ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 19 publications
7
33
1
10
Order By: Relevance
“…Meanwhile, findings of Buscemi et al 28.4% were near to our finding [10]. In the other hand this finding do not compare well with that of other countries such as Adad et al 17.3% -50% (during four decades), and Murta et al 17.8% which may be related to the climatic, geographical and cultural living conditions [11,12].…”
Section: Discussioncontrasting
confidence: 87%
“…Meanwhile, findings of Buscemi et al 28.4% were near to our finding [10]. In the other hand this finding do not compare well with that of other countries such as Adad et al 17.3% -50% (during four decades), and Murta et al 17.8% which may be related to the climatic, geographical and cultural living conditions [11,12].…”
Section: Discussioncontrasting
confidence: 87%
“…Since koilocytosis usually represents the presence of human papillomavirus, [14][15][16] it is believed that the presence of the virus would, in some manner, be a cofactor for infections by other pathogenic or opportunistic microorganisms. 17 These opportunistic agents would be favored by imbalances in the vaginal flora. 18 According to Edwards, 1 Escherichia coli was the species most associated with bacterial vaginitis, although in the present series, it was found that Staphylococcus aureus was the agent most frequently causing it.…”
Section: Discussionmentioning
confidence: 99%
“…could activate the latent infection by HPV. 11,17 The use of molecular biology may be capable of ascertaining associations between genetic and immunological factors and the presence of potentially pathogenic microorganisms. 20 cONclusiONs On the basis of these results, it was found that the prevalence of fungal and parasitic vulvovaginitis seems to be higher in patients with koilocytosis, while the vaginal bacterial flora was not significantly associated with cell abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…A positive relationship between BV and HPV was observed in a population of sex workers, which was very different from our sample group (21) . Murta et al (20) also found an association between vaginosis and papillomavirus; however, this study used a cytological diagnosis of HPV, which is significantly less sensitive than HC2.…”
Section: Discussionmentioning
confidence: 85%